Diversity of freshwater fish in Jabodetabek (rivers and lakes), Indonesia - NOER SARIFAH AINY; LUTHFIRALDA SJAHFIRDI; MUFTI PATRIA PETALA; HARINALDI HARINALDI (Society for Indonesian Biodiversity, 2026)
Abstract. Ainy NS, Sjahfirdi L, Petala MP, Harinaldi. 2026. Diversity of freshwater fish in Jabodetabek (rivers and lakes), Indonesia. Biodiversitas 27 (5): d270518. https://doi.org/10.13057/biodiv/d270518. In the Jabodetabek (Jakarta, Bogor, Depok, Tangerang and Bekasi) metropolitan area of Indonesia, this study assessed the structure of freshwater fish communities in interconnected river and lake ecosystems. The focus was on diversity, native-alien composition, and spatial homogenization along upstream-downstream river gradients and inlet-outlet lake zonation. From August to December 2024, fish were collected from three rivers (Ciliwung, Cisadane, and Cileungsi) and three lakes (Tonjong, Tunggilis, and Suradita) using standardized plots and various types of fishing gear. The data were then analyzed for species richness, abundance, diversity, dominance, PERMANOVA, and beta dispersion. Rivers had more species (38) and individuals (2,471) than lakes (27 species and 1,375 individuals), but they also had a higher proportion of alien fish (64.90%) than lakes (50.20%). Oreochromis niloticus and Pterygoplichthys pardalis were the dominant invasive species in rivers, especially in the middle and downstream sections. Oreochromis niloticus and Amphilophus labiatus were the dominant invasive species in lakes, particularly in inlet zones and disturbed areas. Lakes showed more pronounced cross-zone biotic homogenization, whereas rivers exhibited higher spatial turnover. However, some degraded areas also showed signs of homogenization. The findings suggest that biological invasions are reducing the complexity of Jabodetabek’s freshwater ecosystems and pushing native species into less disturbed habitats. To reduce the risk of reinvasion and protect freshwater biodiversity, management should focus on controlling the most widespread invasive species, preventing new introductions, restoring habitats, and protecting existing native fish refuges.